Knowledge management the death of wisdom : why our companies have lost it, and how they can get it back - Kransdorff, Arnold ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2012)
Conceived less than 20 years ago, Knowledge Management (KM) is the business discipline about which managers perhaps know the least. Having spent pots of money investing in it, the benefits are still marginal. This is because practitioners are still feeling their way. Now that the boom days are temporarily over, it is timely that KM can be more fully exploited, for it conceals an application that is indispensable for the foreseeable struggle ahead--and after, including an overlooked way out of the credit crash dilemma facing those dogmatic decision makers juggling the option between austerity and growth. It's not rocket science. It's a way of doing both, in this case by refocusing on the old-fashioned notion of productivity implied by this book's Chapter 2 heading: Getting from A to B without going via Z. Not the productivity that comes from cutbacks and austerity but the type that frontruns improved competitiveness, sales, and growth.
Author's credentials -- Preface -- 1. The race where every sprinter drops the baton -- 2. Getting from A to B without going via Z -- 3. Here today, gone tomorrow -- 4. Opportunity knocks for business education -- 5. "I forgot to remember!" -- 6. The smart march to wisdom -- 7. How the baton was passed -- 8. Way to go -- Appendix. Checkbooks and boxing gloves: origins of the author's interest -- Notes -- References -- Bibliography -- Index.
Part of: 2012 digital library.
Includes bibliographical references (p. 123-134) and index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Knowledge management; wisdom; growth; competitiveness; Experiential Learning; Knowledge Management (KM); Organizational Memory (OM); productivity growth; decision making; human resources; The Learning Organization; flexible labor market; job continuity; corporate amnesia; continuous improvement; knowledge transfer; knowledge preservation; action learning; after-action reviews; innovation; business education; experience; corporate history; economic history; cliometrics; case studies; exit interviews; oral debriefing; explicit knowledge; tacit knowledge; Experience-Based Management (EBM); lessons learned; repeated mistakes; reinvented wheels; hindsight; evolution; disenfranchise; benchmarking; mentoring; Brazil, Russia, India, China, and Korea (BRICK); MBA; Electronic books